Hippocampal network activity is transiently altered by induction of long-term potentiation in the dentate gyrus of freely behaving rats - Bikbaev, Arthur; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2007)
A role for oscillatory activity in hippocampal neuronal networks has been proposed in sensory encoding, cognitive functions and synaptic plasticity. In the hippocampus, theta (5–10 Hz) and gamma (30–100 Hz) oscillations may provide a mechanism for temporal encoding of information, and the basis for formation and retrieval of memory traces. Long-term potentiation (LTP) of synaptic transmission, a candidate cellular model of synaptic information storage, is typically induced by high-frequency tetanisation (HFT) of afferent pathways. Taking into account the role of oscillatory activity in the processing of information, dynamic changes may occur in hippocampal network activity in the period during HFT and/or soon after it. These changes in rhythmic activity may determine or, at least, contribute to successful potentiation and, in general, to formation of memory. We have found that short-term potentiation (STP) and LTP as well LTPfailure are characterised with different profiles of changes in theta and gamma frequencies. Potentiation of synaptic transmission was associated with a significant increase in the relative theta power and mean amplitude of theta cycles in the period encompassing 300 seconds after HFT. Where LTP or STP, but not failure of potentiation, occurred, this facilitation of theta was accompanied by transient increases in gamma power and in the mean amplitude of gamma oscillations within a single theta cycle. Our data support that specific, correlated changes in these parameters are associated with successful synaptic potentiation. These findings suggest that changes in theta-gamma activity associated with induction of LTP may enable synaptic information storage in the hippocampus.